A clickable NHC–Au(i)-complex for the preparation of stimulus-responsive metallopeptide amphiphiles. Issue 68 (9th August 2018) - Lewe, V.; Preuss, M.; Woźnica, E. A.; Spitzer, D.; Otter, R.; Besenius, P.
Abstract : We report the synthesis of an alkyne functionalised NHC–Au(i )-complex which is conjugated with amphiphilic oligopeptides using a copper(i ) catalysed cycloaddition. Abstract : We report the synthesis of an alkyne functionalised NHC–Au(i )-complex which is conjugated with amphiphilic oligopeptides using a copper(i ) catalysed cycloaddition. The resulting Au(i )-metalloamphiphiles are shown to self-assemble into charge-regulated stimulus-responsive supramolecular polymers in water via a weakly cooperative polymerisation mechanism.